Serum and urine vitamin D metabolite analysis in early preeclampsia. Issue 1 (January 2018) - Tamblyn, J A; Jenkinson, C; Larner, D P; Hewison, M; Kilby, M D
Abstract : Vitamin D deficiency is common in pregnant women and may contribute to adverse events in pregnancy such as preeclampsia (PET). To date, studies of vitamin D and PET have focused primarily on serum concentrations vitamin D, 25-hydroxyvitamin D3 (25(OH)D3) later in pregnancy. The aim here was to determine whether a more comprehensive analysis of vitamin D metabolites earlier in pregnancy could provide predictors of PET. Using samples from the SCOPE pregnancy cohort, multiple vitamin D metabolites were quantified by liquid chromatography–tandem mass spectrometry in paired serum and urine prior to the onset of PET symptoms. Samples from 50 women at pregnancy week 15 were analysed, with 25 (50%) developing PET by the end of the pregnancy and 25 continuing with uncomplicated pregnancy. Paired serum and urine from non-pregnant women ( n  = 9) of reproductive age were also used as a control. Serum concentrations of 25(OH)D3, 25(OH)D2, 1, 25(OH)2 D3, 24, 25(OH)2 D3 and 3-epi-25(OH)D3 were measured and showed no significant difference between women with uncomplicated pregnancies and those developing PET. As previously reported, serum 1, 25(OH)2 D3 was higher in all pregnant women (in the second trimester), but serum 25(OH)D2 was also higher compared to non-pregnant women. In urine, 25(OH)D3 and 24, 25(OH)2 D3 were quantifiable, with both metabolites demonstrating significantly lower ( P  < 0.05) concentrations of both of these metabolites in those destined to develop PET. These data indicate that analysis of urinary metabolites provides an additional insight into vitamin D and the kidney, with lower urinary 25(OH)D3 and 24, 25(OH)2 D3 excretion being an early indicator of a predisposition towards developing PET.